How Germany unified and the EU enlarged negotiating the accession through transplantation and adaptation - Novotná, Tereza 1981- (New perspectives in German political studies, 2015)
"Based on original empirical research that includes 90 interviews with key leaders, this book compares and contrasts negotiations during the processes of German unification and Eastern enlargement of the EU, with particular attention to the Czech Republic. It develops two models of political integration and suggests that such integration can take place by means of a take-over (Transplantation), or by the joining entity adjusting to the norms and institutions of the accepting party (Adaptation). In addition to an exploration of these two different models and a detailed examination of the two cases, the book points to other historical examples of Transplantation and Adaptation and formulates lessons for where future research might travel, temporarily and geographically, in the cases of other political integrations. Providing new insights into German unification and European integration, this text is key reading for academics, advanced undergraduate and graduate students in EU Politics, as well as policy-makers and the wider public"--